PENGARUH WAKTU SIMULASI TRANSPORTASI TERHADAP KUALITAS BUAH TOMAT ( Lycopersicum Esculentum Mill ) - Yulia Firanty Gultom; Setyadi Gumaran; Ni Wayan Arya Utari (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Tomatoes have a short storage time and are easily damaged. Tomatoes have thin skin and high water content, so the commodity will quickly deteriorate after being treated with simulated transportation and storage processes. This research aims to analyze the effect of the simulation time on weight loss, mechanical damage, color, hardness, and total soluble solids of tomatoes and to explain the effect of simulation time treatment on weight loss, mechanical, damage, color, hardness, and total soluble solids of tomatoes during storage. This study used a completely randomized design using transportation simulation vibration times (30 minutes and 90 minutes) and controls not given vibration treatment using three repetitions and kept for 8 days. This research shows that the treatment of variations in vibration time affects mechanical damage and weight loss. Vibration time of 30 minutes on day 8 I had mechanical damage of 15,38%, weight loss of 5,77%, color L* 40,88, color a* 20,06, hardness 11,88, and total dissolved solids 4,25. Vibration time of 90 minutes has mechanical damage of 20,51%, weight loss of 7,53%, color L* 40,63, color a* 21,21, hardness 11,65 and total dissolved solids 4,33.